Age-related alterations and senescence of mesenchymal stromal cells: Implications for regenerative treatments of bones and joints. (September 2021) - Zupan, Janja; Strazar, Klemen; Kocijan, Roland; Nau, Thomas; Grillari, Johannes; Marolt Presen, Darja
Highlights: Aging presents a major risk factor for osteoarthritis and osteoporosis. Aging decreases the regenerative potential of mesenchymal stromal cells (MSCs). Studies have demonstrated changes to MSCs in joint-degenerative disorders. Understanding of MSC actions enables the development of new cell-free therapies. Abstract: The most common clinical manifestations of age-related musculoskeletal degeneration are osteoarthritis and osteoporosis, and these represent an enormous burden on modern society. Mesenchymal stromal cells (MSCs) have pivotal roles in musculoskeletal tissue development. In adult organisms, MSCs retain their ability to regenerate tissues following bone fractures, articular cartilage injuries, and other traumatic injuries of connective tissue. However, their remarkable regenerative ability appears to be impaired through aging, and in particular in age-related diseases of bones and joints. Here, we review age-related alterations of MSCs in musculoskeletal tissues, and address the underlying mechanisms of aging and senescence of MSCs. Furthermore, we focus on the properties of MSCs in osteoarthritis and osteoporosis, and how their changes contribute to onset and progression of these disorders. Finally, we consider current treatments that exploit the enormous potential of MSCs for tissue regeneration, as well as for innovative cell-free extracellular-vesicle-based and anti-aging treatment approaches.